Incorporation of pharmacogenetic testing into medication therapy management. (November 2015) - Haga, Susanne B; Moaddeb, Jivan; Mills, Rachel; Patel, Mahesh; Kraus, William; Allen LaPointe, Nancy M
Aim: To assess feasibility and patient satisfaction with a pharmacist-delivered medication therapy management (MTM) plus pharmacogenetic (PGx) testing service.Methods: Thirty patients from a cardiology outpatient clinic were enrolled to attend two MTM sessions, undergo PGx testing and complete pre- and post-intervention surveys. Outcome measures included duration of MTM sessions, clinical application of test results, self-reported medication adherence, patient recall of results and perceived value of testing and MTM.Results: Overall, patients were very satisfied with the MTM plus PGx testing service. About half of participants (47%) were able to accurately recall their PGx test results. Comparable to MTM without PGx testing, the first MTM session averaged 40 min and the follow-up MTM session averaged 15 min.Conclusion: PGx testing incorporated into a clinical MTM service offered by pharmacists may be a feasible delivery model and is satisfactory to patients.